2020
DOI: 10.1002/er.5305
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of a direct absorption solar collector using copper oxide porous foam and nanofluid

Abstract: The current research proposes the idea of using water-saturated metal oxide foams and water-based nanofluids as solar absorber in the direct absorption solar collectors (DASCs). Specifically, the novel solar collector design utilizes copper oxide (CuO) porous foam and nanoparticle with high optical properties and is expected to have enhanced thermal performance than the conventional collectors utilizing pure water. The finite volume technique is used to solve the governing equations of flow and heat transfer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…In nanofluids, the suspended nanoparticles can boost the absorption coefficient of base fluids if the absorption performance of nanoparticles is substantially higher than that of the base fluid. Water‐based nanofluids have been widely investigated until recently using various nanoparticles, such as metal nanoparticles (eg, gold nanorod 5 and Fe 6 ), metal oxide nanoparticles (eg, WO 3 , 7 Al 2 O 3, 8 and Cu oxide porous foam 9 ), carbon nanoparticles (eg, MWCNT 10 ), hybrid (CuO/MWCNT 11 and Fe 3 O 4 /carbon nanoparticles 12 ), and core‐shell (silica‐gold 13,14 ) nanoparticles. For example, water‐based plasmonic nanofluids were synthesized with three types of nanorods that have different aspect ratios for broadband absorption 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In nanofluids, the suspended nanoparticles can boost the absorption coefficient of base fluids if the absorption performance of nanoparticles is substantially higher than that of the base fluid. Water‐based nanofluids have been widely investigated until recently using various nanoparticles, such as metal nanoparticles (eg, gold nanorod 5 and Fe 6 ), metal oxide nanoparticles (eg, WO 3 , 7 Al 2 O 3, 8 and Cu oxide porous foam 9 ), carbon nanoparticles (eg, MWCNT 10 ), hybrid (CuO/MWCNT 11 and Fe 3 O 4 /carbon nanoparticles 12 ), and core‐shell (silica‐gold 13,14 ) nanoparticles. For example, water‐based plasmonic nanofluids were synthesized with three types of nanorods that have different aspect ratios for broadband absorption 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nanofluids are promising alternatives to the commonly used fluids in DASCs. 11,12 Various nanoparticles, ranging from carbon materials (such as graphene, 13,14 carbon black, 15 carbon nanotube, 16,17 and graphite 18 ), metals (such as Cu, 19 Ag, 20 and Au 21 ), metal oxides (such as Fe 3 O 4, 22 CuO, 23,24 and TiO 2 25 ), carbides (such as SiC 26 and ZrC 27 ), and nitrides (such as BN 28 and TiN 29 ), have been evaluated for light absorption enhancement. However, a mono nanoparticle can usually improve the absorption in a certain bandwidth of the solar spectrum, leading to limited performance enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…20 Eltaweel et al 21 selected 0.25 wt% multiwalled carbon nanotube/water nanofluid as the heat transfer medium of the solar collector, and found that the heat transfer efficiency was 7% higher than that of pure water. Esmaeili et al 22 compared the effects of different heat transfer medium on the performance of solar collectors. Compared with water, they concluded that the thermal efficiency of using CuO nanofluids and metal oxide foam as heat transfer medium increased by 26.8% and 23.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%